Odpowiedzi

2010-04-15T18:29:55+02:00
4(x+2)-3(y-1)=x+y-3
3(x-4)-2(y-2)=4(x-y)+4

4x+8-3y+3=x+y-3
3x-12-2y+4=4x-4y+4

4x-3y-x-y=-8-3-3
3x-2y-4x+4y=4-4+12

3x-4y=-14
-x+2y=12 \*3

+[ 3x-4y=-14
+[ -3x+2y=36
___________________________
2y-4y=36-14
-2y=22 \ :-2
y=-10




4(x+2)-3(y-1)=x+y-3
3(x-4)-2(y-2)=4(x-y)+4

4x+8-3y+3=x+y-3
3x-12-2y+4=4x-4y+4

4x-3y-x-y=-8-3-3
3x-2y-4x+4y=4-4+12

3x-4y=-14
-x+2y=12 \*2

+ [ 3x-4y=-14
+ [ -2x+4y=24
________________________
3x-2x=24-14
x=10

y=-10
x=10
2010-04-15T18:30:16+02:00
4(x+2)-3(y-1)=x+y-3 /+3
3(x-4)-2(y-2)=4(x-y)+4

4X+8-3Y+6=x+y /-x -y -14
3x-12-2y+4=4x-4y+4 / -4 -4x +4y +12

3x-4y=-14
-x+2y=12 /*2

3x-4y=-14
-2x+4y=24
-----------------
+

x=10

-10+2y=12 /+10
2y=22 /:2
y=11
x=10
2010-04-15T18:48:59+02:00
Zadanie masz w załączniku .... ;)